The Effect Of 5% Da On Blood Glucose Level Using As Irrigant During The Procedure Of Turp - Haque, Mohammed Monowar Ul; Islam, Md Hafizul; Siddique, Syeda Rumman Aktar (Journal of Chittagong Medical College Teachers' Association, 2014)
During TURP 1.5% Glycine is a conventional fluid being used as irrigant worldwide. Now a days we are also using 5% Dextrose in Aqua as an irrigant. The aim of this study is to observe the changes in blood glucose level by using 5% dextrose in aqua as an irrigation fluid in TURP for BPH. This was a observational study, conducted on 50 non diabetic BPH patients admitted in the department of Urology, CMCH between 01January, 2006 to 31December, 2007. TURP was done on these patients using.5% Dexrose in Aqua as irrigant. Blood glucose level was recorded pre operatively (24 hr. before opn.), immediate post operatively (5 minutes after surgery) and 24 hour after surgery. Post operative results compared with preoperative values. 2 cases were excluded from current study and rest 48 patients were included into the study. Mean pre operative blood glucose level was 5.97 (+0.60) mmol/L, then it was increased to 6.64 (+0.50) mmol/L,which was significant (P<0.01) in immediate post operative period. The value then reduced to 6.28 (+0.49) mmol/L (P<0.05) 24 hour after surgery. which were within the normal serum glucose level. All the values returned towards pre operative level and the changes were not significant. So, we can do the TURP in remote part of Bangladesh by using 5% DA as an irrigant without fear of blood glucose change. JCMCTA 2013 ; 24 (2): 19-21